The Infra-red Spectra of Complex Molecules - Bellamy, L. author. aut Link
XIX, 433 p.
Keywords: The full revision of this text has presented a number of problems. The basic data have changed little since the second edition, although they have been much extended in depth and in detail. To some extent this has helped to shorten the present text as many controversial issues which needed to be presented at some length have now been resolved so that only the final conclusions need to be given. However, it remains the case that very few new group frequencies have emerged over the past fifteen years and the emphasis of group-frequency studies has tended to shift away from the identification of specific groups towards their other possible uses in the solution of structural and chemical problems. The study of the interplay of mechanical and electronic effects in determining the directions and extents of group-frequency shifts which result from changes in the substituents has told us much about chemical mechanisms themselves, and has opened up new possibilities for the use of group frequencies in areas such as the study of rotational isomerism, the measurement of bond angles, and the use of frequency relationships to derive other chemical and physical properties.